1988
DOI: 10.1038/bjc.1988.209
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between changes in antigen expression and protein synthesis in human melanoma cells after hyperthermia and photodynamic treatment

Abstract: Summary Hyperthermia and photoactivated hematoporphyrin derivative induce a dose-dependent reduction in the expression of the p250 surface melanoma-associated antigen on the human FME cell line. Expression of this glycoprotein antigen was quantitated by immunofluorescence flow cytometry based on the monoclonal antibody 9.2.27. Decrease in antigen expression was followed by a transient increase above the level for untreated cells, before normalization occurred about one week after treatment.These treatment-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…This delay in recovered antigen expression, as compared with resumption of synthesis rate, might be due to heat-induced damage of organelles and structures involved in the transportation of newly synthesized antigens to the cell surface. Reported heat-induced damage of Golgi apparatus support this suggestion (Mitranic et al, 1976;Davies et al, 1988).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This delay in recovered antigen expression, as compared with resumption of synthesis rate, might be due to heat-induced damage of organelles and structures involved in the transportation of newly synthesized antigens to the cell surface. Reported heat-induced damage of Golgi apparatus support this suggestion (Mitranic et al, 1976;Davies et al, 1988).…”
Section: Discussionsupporting
confidence: 61%
“…However, the synthesis rate of total proteins showed a transient increase above normal synthesis rate, suggesting that other proteins might be expressed above normal level. Such transient increase in protein synthesis rate has also been found for other cell lines (Hahn and Shiu, 1985;Davies e l al., 1988), and the synthesis rate of melanoma cells was reported to decrease from the hypernormal synthesis rate at the same time as the expression of melanoma-associated antigen reached normal level (Davies et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…PDT activates several signaling pathways, which in turn alter the expression of many different downstream genes (14). After PDT, inhibition of DNA and RNA polymerases (34,35) and synthesis of DNA, RNA and protein (36,37) have been demonstrated. In vitro studies have shown that PDT can produce single‐ and double‐strand breaks (38–40), sister chromatid exchanges (41,42), chromosome aberrations (43) and mutagenic alterations (38,42,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…PDT activates several signaling pathways, which in turn alter the expression of many different downstream genes (14). After PDT, inhibition of DNA and RNA polymerases (34,35) and synthesis of DNA, RNA and protein (36,37) have been demonstrated. In vitro studies have shown that PDT can produce single-and double-strand breaks (3840), sister chromatid exchanges (4 1,42), chromosome aberrations (43) and mutagenic alterations (38,42,44,45).…”
Section: Discussionmentioning
confidence: 99%